Pengaruh Kualitas Layanan Dan Kepercayaan Terhadap Kepuasan Pelanggan - Zefanya Zefanya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The aim of this study are: Frist, to explore the effect of service quality towards customer satisfaction. Second , to explore the effect of trust towards customer satisfaction. The method of data collection is convenience sampling. The sample of this research are collected from 186 respondent, who used one of these online shops in Jakarta. The technique of data analysis used in this study was regression analysis via the statistical package for social sciences computer programme version 18. The result are: (1) service quality has a positive impact towards customer satisfaction; (2) trust has a positive impact towards customer satisfaction.